CARBONO ORGÂNICO TOTAL E DAS FRAÇÕES DA MATÉRIA ORGÂNICA EM SISTEMA SILVIPASTORIL - BARRETA, Paulo Gabriel Vechetin; SILVA, Jeferson Rogério Marques da; OLIVEIRA, Taine Pereira; RESENDE, João Victor Oliveira; ENSINAS, Simone Candido; BARBOSA, Giselle Feliciani (ANAIS DO ENIC, 2020)
-